A Three-Phase Reduced Switch Count Multilevel Inverter Topology - S. Sivamani; V. Mohan (International Transactions on Electrical Energy Systems)
Multilevel inverters play a vital role in the industrial and renewable energy sectors due to their flexibility in synthesizing sinusoidal waveforms using a low-pass filter with a medium voltage range. It has several drawbacks, such as a higher number of power component requirements and voltage balancing problems. In this study, a new structure for multilevel inverters has been developed to offer good power quality with minimum number of switching devices and gate driver circuits. The proposed structure is configured to operate in symmetrical and asymmetrical configurations for single/three-phase versions. A simulation study using MATLAB/Simulink has been utilized to study the operating characteristics under both configurations. A laboratory prototype has been built to check the feasibility of the proposed structure for real-time applications.